Effect of Chromate Inhibitor on the Corrosion Rate of API 5L Grade B Steel Pipe in the Injection Water - Priyo Tri Iswanto; Ardian Shah; Hizba Muhammad Sadida (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2019)
Corrosion inside the injection water pipe occurs from the Central Injection Facility Station to the wellhead. One way to reduce the rate of corrosion is to add inhibitors. This research is looking for the effect of variations in the concentration of the sodium chromate inhibitor (Na2CrO4) on the corrosion rate of API 5L grade B pipes used in the oil industry, especially in injection water fluids. For comparison, a corrosion rate test was carried out on a 3.5% NaCl solution. The study used an NPS 4 SCH 40 pipe with an outer diameter of 4.5 in (114.3 mm) with a thickness of 0.237in (6.02mm). The concentration parameter of the Sodium Chromate inhibitor used is 0.1; 0.3; 0.5; 0.7 and 0.9%. The study used a corrosion rate test using the potentiodynamic polarization method. The results showed the pipe corrosion rate in the injection water fluid was 0.3307 mpy, and the pipe corrosion rate in the 3.5% NaCl solution was 0.4960 mpy. The addition of chromate inhibitors succeeded in decreasing the corrosion rate. The maximum condition is achieved with the addition of 0.9% inhibitor. In this condition, the corrosion rate of the pipe in the injection water solution is 0.2175 mpy and the corrosion rate of the pipe in the 3.5% NaCl solution is 0.3218 mpy.